Social security: can rattlesnakes reduce acute stress through social buffering? - Martin, Chelsea E.; Fox, Gerad A.; Putman, Breanna J.; Hayes, William K. (Frontiers in Ethology, 2023)
Social buffering comprises the reduction of stress an organism experiences when in the presence of a companion and has been well documented in highly social animals, such as birds and mammals. To date, it has not been reported in reptiles. Rattlesnakes are cryptically social, exhibiting kin recognition and forming subtle social networks in certain contexts. We tested for the presence of social buffering against an acute stressor in 25 wild-caught adult southern Pacific rattlesnakes (Crotalus helleri) by measuring heart rate increase during a standardized disturbance when alone, in the presence of a rope (inanimate object control), and in the presence of a same-sex companion. We further tested for a greater proclivity of social buffering in montane snakes, which overwinter communally, than in lowland snakes, which mostly overwinter alone; and for a greater proclivity in females, which often aggregate during gestation and maternally attend their offspring. Results indicated that the presence of a companion significantly reduced emotional tachycardia (change in heart rate) after disturbance compared to the other treatments. We detected no difference in social buffering proclivity between montane and lowland populations, but lowland snakes exhibited a subdued acute stress response across treatments and had a longer heart rate recovery time. No difference in emotional tachycardia existed between the sexes. This novel study can benefit our understanding of social buffering, including its expression, adaptive roles, and practical applications for captive animals.